*Las dimensiones de lengua y cultura e interculturales en la enseñanza y el aprendizaje de una lengua extranjera - Barbosa, Lúcia Maria de Assunção (Íkala, Revista de Lenguaje y Cultura, 2007)
The process of teaching/learning a foreign language cannot be reduced to the attainment of an instrument for communication. It is an interdisciplinary procedure with the objective of introducing the learner to the symbolic universe in which he wants to participate. This article presents some general considerations involving the cultural dimension in the context of teaching and learning a foreign language. It also touches certain aspects of the word “culture”, demonstrating how it differs from the word “civilization” which predominated for a considerable period of time in the French context of the didactics of foreign language teaching and learning. This lexical shift brought about relevant aspects concerning the belief that language and culture are inseparable elements. Received: 08-03-07 / Accepted: 08-06-07 How to reference this article: Assunção Barbosa, L. M. de. (2007). Las dimensiones de lengua y cultura e interculturales en la enseñanza y el aprendizaje de una lengua extranjera. Íkala. 12(1), pp. 165 – 181.